Literature Review: The Effect of Tin Leaves (Ficus Carca L.) as an Antibacterial Staphylococcus Aureus - Siti Zulfa Angraini; Rachmat Faisal Syamsu; Shulhana Mokhtar (Jurnal EduHealth, 2024)
Staphylococcus aureus is a bacteria that causes infections that must be treated with antibiotics. Another alternative that can be done to deal with this resistance is to use herbal ingredients as the basis for therapy. The development of research on natural ingredients as antibacterials shows that there are plants that have the potential to act as antibacterial agents. Fig leaves or figs (Ficus carica L.) are a plant that has the potential to be an antioxidant, antiviral, anthelmintic and antibacterial. Fig leaf extract (Ficus carica L.) shows antibacterial activity against the growth of several bacteria such as Staphylococcus aureus. This literature aims to determine the effect of fig leaves as an antibacterial against Staphylococcus aureus bacteria. This literature uses a literature review method with the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) protocol. Scientific articles or journals downloaded from PubMed, Garuda Portal, and Google Scholar with SINTA accreditation standards in the 2020-2023 time period found 430 articles in the search results. All articles were selected based on the inclusion criteria, resulting in 20 research articles that would be reviewed. The antibacterial potential of fig leaves in the inhibition zone uses ethanol compounds, phenolic flavonoids, ethyl acetate, nickel oxide nanoparticles and Calcium Oxide Phyto-Nanoparticles (CaONPs) which have been proven effective in inhibiting the growth of Staphylococus aureus. Fig leaves are effectively used as an antibacterial for Staphylococcus aureus, showing that they can prevent the growth of bacteria with several compounds contained therein such as Ethanol extract, Phenolic Flavonoids, Ethyl Acetate, Nickel Oxide Nano Particles and Calcium Oxide Phyto-Nanoparticles (CaONPs) which have antibacterial properties.